Beam combining of a broadly and continuously tunable quantum cascade laser - Sun, Fangyuan (2023)
We report a cost-efficient method to demonstrate the beam combining of five laser elements in an array of tunable slot waveguide quantum cascade lasers in the mid-infrared region at around 10 µm. An aspherical lens with five fine-tuned mini mirrors was employed to collimate the individual beams from the laser array. To verify the feasibility of this beam combining approach, the combined beams were coupled into a hollow-core fiber gas cell with a low numerical aperture (N.A.) of 0.03 and a coupling efficiency >= 0.82, for gas sensing of binary compound gases of ammonia and ethylene simultaneously.